2011
DOI: 10.1007/s00701-011-0968-7
|View full text |Cite
|
Sign up to set email alerts
|

Delayed caroticocavernous fistula after stent-assisted coil embolization of intracavernous carotid aneurysm: should we manage conservatively?

Abstract: Constructive endovascular techniques remain the mainstay for the treatment of cavernous carotid aneurysms due to their efficacy. However, they do harbor risks of complications, such as thromboembolic events, arterial injuries, and vessel occlusions. A 58-year-old lady presented with delayed caroticocavernous fistula (CCF) 1 month after stent-assisted coil embolization of a cavernous carotid aneurysm (CCA). Following this, her caroticocavernous fistula resolved spontaneously with no further intervention. Our ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…While no patient treated with PED in PUFS experienced aneurysm rupture that resulted in subarachnoid hemorrhage to date, one patient developed a subacute carotid cavernous fistula after PED treatment of a cavernous segment aneurysm-an untoward outcome also infrequently known to complicate stent-assisted coil treatment of cavernous segment aneurysms (35). Rupture of previously unruptured intradural aneurysms has also been described (31,36,37) after treatment with parent vessel occlusion and coil placement, however, as with endoluminal devices such as PED, the causative mechanism of this adverse occurrence remains obscure.…”
Section: Discussionmentioning
confidence: 99%
“…While no patient treated with PED in PUFS experienced aneurysm rupture that resulted in subarachnoid hemorrhage to date, one patient developed a subacute carotid cavernous fistula after PED treatment of a cavernous segment aneurysm-an untoward outcome also infrequently known to complicate stent-assisted coil treatment of cavernous segment aneurysms (35). Rupture of previously unruptured intradural aneurysms has also been described (31,36,37) after treatment with parent vessel occlusion and coil placement, however, as with endoluminal devices such as PED, the causative mechanism of this adverse occurrence remains obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Another rare complication after flow diversion for the treatment of carotid cavernous aneurysms is the delayed rupture of a cavernous carotid aneurysm leading to the development of a carotid-cavernous fistula. This was noted in PUFS and has been noted with stent assisted coiling in the past [63].…”
Section: Delayed Aneurysmal Rupturementioning
confidence: 54%
“…Chan et al 21 reported on a CCA that was treated with a Neuroform stent and Axium coils. The patient presented at 1 month postoperatively with proptosis, chemosis, and ophthalmoplegia and angiography revealed a CCF.…”
Section: Discussionmentioning
confidence: 99%